Rola skutecznej komunikacji chory-personel medyczny w procesie leczenia pacjenta hospitalizowanego = The role of effective communication between patient and medical staff in the process of inpatient care treatment - Anna Maria Dobosiewicz; Teresa Zmaczyńska; Marta Podhorecka; Walery Zukow (Kazimierz Wielki University, 2016)
Dobosiewicz Anna Maria, Zmaczyńska Teresa, Podhorecka Marta, Zukow Walery. Rola skutecznej komunikacji chory-personel medyczny w procesie leczenia pacjenta hospitalizowanego = The role of effective communication between patient and medical staff in the process of inpatient care treatment. Journal of Education, Health and Sport. 2016;6(9):789-796. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.159105 http://ojs.ukw.edu.pl/index.php/johs/article/view/3902       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 24.09.2016.       Rola skutecznej komunikacji chory-personel medyczny w procesie leczenia pacjenta hospitalizowanego   The role of effective communication between patient and medical staff in the process of inpatient care treatment   Anna Maria Dobosiewicz1, Teresa Zmaczyńska1, Marta Podhorecka1, Walery Zukow2   1Katedra i Klinika Geriatrii, Collegium Medicum UMK, Toruń, Bydgoszcz, Polska/ Nicolaus Copernicus University in Toruń, Collegium Medicum in Bydgoszcz, Department of Geriatrics,  Poland 2Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Polska/ Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland   Streszczenie -  Celem artykułu jest zaprezentowanie metod i sposobów komunikowania się z pacjentem oraz przedstawienia reakcji obronnych pacjentów.  W komunikacji z pacjentem możemy wyróżnić mowę werbalną i niewerbalną. Właściwe używanie zarówno jednej jak i drugiej w znaczący sposób może usprawnić komunikację z pacjentem hospitalizowanym. Dodatkowo znajomość mechanizmów obronnych pacjentów  przyczynia się do ułatwienia komunikacji  na drodze "chory - personel medyczny". Abstract-  The purpose of the article is to show the methods and ways  in communications with patients and present their  defense mechanisms. Verbal and nonverbal speech can be distinguish in communication with patients.  Using them in correct way can expedite the communication with inpatients. In addition, knowing the patient defense mechanisms, the communication can be easier between  patient and medical staff.   Słowa klucze-  komunikacja, mowa werbalna, mowa niewerbalna Key words -  communication, verbal speech,  nonverbal speech